Z dziejów synkretyzmu filozoficznego w epoce renesansu — Jana Grotowskiego "Socrates albo o szlachectwie rozmowa..." - Raubo, Agnieszka (My University, 2011)
The article discusses the philosophical syncretism of the Renaissance time period in a lesser known sixteenth century text of Jan Grotowski (Grotowski): "Socrates albo o szlachectwie rozmowa". The author focuses on a description of the parties involved in the dispute, i.e. Socrates, Diogenes and Themistocles. The description of the interlocutors refers both to their antique and Renaissance descriptions. In addition, the issue of nobleness that comes from birth and the one that comes from living a good life is discussed. The notion of virtue as it was presented in Grotowski’s work is outlined, as well as the relations between the body, soul and the spirit included in it that influence the interpretation of the notion “nobleness”.
From the history of philosophical syncretism in Renaissance: Jan Grotowski’s "Socrates albo o szlachectwie rozmowa"
Keywords: Renaissance; Antiquity; syncretism; philosopher; nobleness